Wastewater antibody signatures reflect SARS-CoV-2 infection and immunization patterns in the population - Dhammika Leshan Wannigama; Mohan Amarasiri; Phatthranit Phattharapornjaroen; Cameron Hurst; Charin Modchang; John Giles; Jillian Gauld; Tanakorn Chantanasaro; Kazuhiko Miyanaga; Longzhu Cui; Stefan Fernandez; Hirotake Mori; et al. (Water Research, 2026)

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

Safe vitrification of ovarian tissue samples in sealed cryobags - Binnur Eroglu; Lawrence C. Layman; James D. Benson; Adam Z. Higgins; Ali Eroglu (Cryobiology, 2025)

Temporal Changes to Migratory Fuel Load in Migratory Birds Across Europe - Jennifer Anne Border; Robert A. Robinson; James W. Pearce‐Higgins; Chris M. Hewson; Christine Howard; Philip A. Stephens; Stephen G. Willis; Jan A. C. von Rönn; Pierre‐Yves Henry; Romain Lorrilliere; Lorenzo Serra; Simona Imperio; et al. (Global Change Biology, 2025)
Climate change is a major threat to biodiversity, and migratory animals are particularly vulnerable, due partly to their reliance upon good resource availability across a network of sites at specific times. Migrants perform vital ecosystem functions, transferring significant resources across large spatial scales, but the impacts of climate change on the ability of individuals to complete these journeys are poorly studied. Collecting the large‐scale and long‐term data on the condition of individuals during migration to address this is challenging, but in migratory birds, we have a model system for which a large network of ringers (banders) collect individual data on body size and mass, enabling variation in body condition to be tracked. We used long‐term ringing data on 33 Afro–Palearctic migratory bird species at 286 sites across Europe to demonstrate a large‐scale decrease in migratory fuel loads during autumn over the last 40 years, but not in spring. Declines were strongest across southern Europe and linked to rising temperatures. The timing of autumn fuelling has also shifted, occurring earlier at northern sites and later at southern sites. These relationships varied depending on diet and breeding cycle length. Obligate insectivores were more constrained by temperature in the timing and magnitude of fuelling than frugivores. Species with short breeding cycles departed later at southern sites in warmer years, likely reflecting an extended breeding season. Altogether, these latitudinally varying findings suggest a trade‐off between maximising productivity or maximising adult survival as climate drives changing constraints on breeding season length and resource availability. Similar climate‐induced trade‐offs may be happening in other migratory taxa with the potential to influence population trends.

Alignment between Duplex Sequencing and transgenic rodent mutation assay data in the assessment of in vivo NDMA-induced mutagenesis - Anne L. Ashford; Daniela Nachmanson; John W. Wills; Jacob E. Higgins; Thomas H. Smith; Kevin C. Vavra; Farah A. Dahalan; Jonathan Howe; Joanne M. Elloway; Jesse J. Salk; Ann Doherty; Anthony M. Lynch (Archives of Toxicology, 2025)

P28-35 Xylene: weight of evidence approach case study to determine the need for an extended one generation reproductive study with a developmental neurotoxicity animal cohort - L. Higgins; C. Haines; F. Faulhammer; M. Rooseboom; N. Aygun Kocabas; J.H. Arts; A. Cordova; E. Freeman; M. Nahar; E. Richmond; S. Schneider; K. Morris-Schaffer (Toxicology Letters, 2025)

P35-10 In vitro metabolism of ethylbenzene and xylene isomers in rat liver S9 - C. Haines; L. Higgins; N. Aygun Kocabas; M. Rooseboom; F. Faulhammer; J. Sanchez; S. Schuchardt; K. Bluemlein (Toxicology Letters, 2025)

Disentangling global geochemical signals from local diagenetic alteration in shallow-water marine carbonates during OAE1a - Matthew D. Nadeau; Jack G. Murphy; Cedric J. Hagen; Ziman Wu; Alliya A. Akhtar; Anne-Sofie Ahm; Daniel A. Stolper; Adam C. Maloof; John A. Higgins (Earth and Planetary Science Letters, 2025)

Acute effects of psilocybin on attention and executive functioning in healthy volunteers: a systematic review and multilevel meta-analysis - P. Yousefi; Morten P. Lietz; F. J. O’Higgins; R. C. A. Rippe; G. Hasler; M. van Elk; S. Enriquez-Geppert (Psychopharmacology, 2025)
Rationale Psilocybin shows promise for treating neuropsychiatric disorders. However, insight into its acute effects on cognition is lacking. Given the significant role of executive functions in daily life and treatment efficacy, it is crucial to evaluate how psilocybin influences these cognitive domains. Objectives This meta-analysis aims to quantify the acute effects of psilocybin on executive functions and attention, while examining how dosage, timing of administration, cognitive domain, and task characteristics moderate these effects. Methods A systematic review and multilevel meta-analysis were conducted on empirical studies assessing psilocybin’s acute effects on working memory, conflict monitoring, response inhibition, cognitive flexibility, and attention. Effect sizes for reaction time (RT) and accuracy (ACC) were calculated, exploring the effects of timing (on-peak defined as 90–180 min post-administration), dosage, cognitive function categories, and task sensitivity to executive functions as potential moderators. Results Thirteen studies (42 effect sizes) were included. In the acute phase, psilocybin increased RTs (Hedges' g = 1.13, 95% CI [0.57, 1.7]) and did not affect ACC (Hedges' g = -0.45, 95% CI [-0.93, 0.034]). Effects on RT were dose dependent. Significant between-study heterogeneity was found for both RT and ACC. Task sensitivity to executive functions moderated RT effects. Publication bias was evident, but the overall effect remained significant after adjustment for this. Conclusions Our meta-analysis shows that psilocybin impairs executive functions and results in a slowing down of RT. We discuss potential neurochemical mechanisms underlying the observed effects as well as implications for the safe use of psilocybin in clinical and experimental contexts.

A horizon scan of biological conservation issues for 2025 - William J. Sutherland; Peter N.M. Brotherton; Holly M. Butterworth; Stewart J. Clarke; Tammy E. Davies; Nigel Doar; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jonathan Hughes; et al. (Trends in Ecology & Evolution, 2025)

Carbon isotopic record of a platform-to-basin transect through the Permian Reef Complex (Guadalupian) in the Delaware Basin of Texas and New Mexico - Page C. Quinton; Michael C. Rygel; Anah Bogdan; Lauryn Higgins; Ty Paddock; Caroline Winstead; Chelsea Wright (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

P06-08 The short-term toxicity and metabolome of Dicyclopentadiene - C. Haines; B. van Ravenzwaay; N. Aygun Kocabas; F. Faulhammer; B. Flick; V. Giri; S. Sperber; M.G. Penman; L.G. Higgins; H. Kamp; M. Rooseboom (Toxicology Letters, 2024)

A Qualitative Exploration of Spanish-Speaking Latina Women’s Experiences Participating in WIC Before and During the COVID-19 Pandemic - Carlos R. Soto Díaz; Lindsey Smith Taillie; Isabella C.A. Higgins; Ana Paula C. Richter; Cassandra R. Davis; Molly De Marco; Marissa G. Hall; Shu Wen Ng; Emily W. Duffy (Journal of the Academy of Nutrition and Dietetics, 2024)

Advanced optical photothermal infrared spectroscopy for comprehensive characterization of microplastics from intravenous fluid delivery systems - Abhrajyoti Tarafdar; Junhao Xie; Aoife Gowen; Amy C. O'Higgins; Jun-Li Xu (Science of The Total Environment, 2024)

Why a strategic shift in action is needed to recognise and empower Indigenous plant pathology knowledge and research - H. Ehau-Taumaunu; N. M. Williams; A. Marsh; N. W. Waipara; C. M. Higgins; A. D. W. Geering; C. H. Mesarich; L. A. Rigano; B. A. Summerell; G. I. Johnson; P. Williamson; R. M. MacDiarmid (Australasian Plant Pathology, 2024)
Plant pathology researchers play a pivotal role in thought leadership and its translation to action regarding the recognition and demonstration of the value of Indigenous knowledge and science. For many scientists, navigating the space of Indigenous rights and perspectives is challenging. In pursuit of a cultural shift in research and development within the field of plant pathology, the 2019–2021 Management Committee of the Australasian Plant Pathology Society (APPS) undertook a review and modernization of the Society’s Constitution. The aim was to ensure its alignment with principles that foster inclusivity of Indigenous peoples in the development and implementation of relevant research projects impacting their communities. Additionally, a dynamic repository of guidelines and resources was compiled. These resources are designed to assist plant pathologists, while respecting and not superseding the guidance provided by local Indigenous researchers, practitioners, and advisors. The collective efforts of plant pathologists hold immense potential in championing Indigenous Peoples and their rights, steering the field toward a more inclusive and equitable future. This paper builds upon the thesis presented in the APPS Presidential Address at the Biennial APPS Conference in 2021, held virtually in lutruwita (Tasmania) on the unceded lands of the Palawa people. It underscores the potential impact when plant pathologists unite in advocating for Indigenous Peoples and their rightful place within the field.

Global patterns of allochthony in stream–riparian meta‐ecosystems - Daniel C. Allen; James Larson; Christina A. Murphy; Erica A. Garcia; Kurt E. Anderson; Michelle H. Busch; Alba Argerich; Alice M. Belskis; Kierstyn T. Higgins; Brooke E. Penaluna; Veronica Saenz; Jay Jones; et al. (Ecology Letters, 2024)
Ecosystems that are coupled by reciprocal flows of energy and nutrient subsidies can be viewed as a single “meta‐ecosystem.” Despite these connections, the reciprocal flow of subsidies is greatly asymmetrical and seasonally pulsed. Here, we synthesize existing literature on stream–riparian meta‐ecosystems to quantify global patterns of the amount of subsidy consumption by organisms, known as “allochthony.” These resource flows are important since they can comprise a large portion of consumer diets, but can be disrupted by human modification of streams and riparian zones. Despite asymmetrical subsidy flows, we found stream and riparian consumer allochthony to be equivalent. Although both fish and stream invertebrates rely on seasonally pulsed allochthonous resources, we find allochthony varies seasonally only for fish, being nearly three times greater during the summer and fall than during the winter and spring. We also find that consumer allochthony varies with feeding traits for aquatic invertebrates, fish, and terrestrial arthropods, but not for terrestrial vertebrates. Finally, we find that allochthony varies by climate for aquatic invertebrates, being nearly twice as great in arid climates than in tropical climates, but not for fish. These findings are critical to understanding the consequences of global change, as ecosystem connections are being increasingly disrupted.

Shallow carbonate geochemistry in the Bahamas since the last interglacial period - Stacey Edmonsond; Matthew D. Nadeau; Andrew C. Turner; Ziman Wu; Emily C. Geyman; Anne-Sofie C. Ahm; Blake Dyer; Sergey Oleynik; David McGee; Daniel A. Stolper; John A. Higgins; Adam C. Maloof (Earth and Planetary Science Letters, 2024)

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

A machine learning approach to predicting plant available phosphorus that accounts for soil heterogeneity and regional variability - Rebecca L. Hall; Felipe Bachion de Santana; Eric C. Grunsky; Margaret A. Browne; Victoria Lowe; Mairéad Fitzsimons; Suzanne Higgins; Vincent Gallagher; Karen Daly (Journal of Soils and Sediments, 2024)
Purpose Mehlich-3 extractable P, Al, Ca, and Fe combined with pH can be used to help explain soil chemical processes which regulate P retention, such as the role of Al, Ca, Fe, and pH levels in P fixation and buffering capacity. However, Mehlich-3 is not always the standard test used in agriculture. The objective of this study is to assess the most reliable conversion of Mehlich-3 Al, Ca, Fe, and P and pH into a commonly used soil P test, Morgan’s P, and specifically to predict values into decision support for fertiliser recommendations. Methods A geochemical database of 5631 mineral soil samples which covered the northern area of Ireland was used to model soil test P and P indices using Mehlich-3 data. Results A random forest machine learning algorithm produced an R 2 of 0.96 and accurately predicted soil P index from external validation in 90% of samples (with an error range of ± 1 mg L −1 ). The model accuracy was reduced when predicted Morgan’s P concentration was outside of the sampled area. Conclusions It is recommended that random forest is used to produce Mehlich-3 conversions, especially when data covers large spatial scales with large heterogeneity in soil types and regional variations. To implement conversion models into P testing regimes, it is recommended that representative soil types/geochemical attributes are present in the dataset. Furthermore, completion of a national scale geochemical survey is needed. This will enable accurate predictions of Morgan’s P concentration for a wider range of soils and geographical scale.

Toddler Milk Perceptions and Responses to Front-of-Package Claims and Product Warnings: A Qualitative Study of Caregivers of Toddlers - Ana Paula C. Richter; Emily W. Duffy; Isabella C.A. Higgins; Clare Barrington; Stephanie L. Martin; Kathryn H. Aquilina; Mirian I. Avendaño-Galdamez; Marissa G. Hall (Journal of the Academy of Nutrition and Dietetics, 2023)

Adopting duplex sequencing technology for genetic toxicity testing: A proof-of-concept mutagenesis experiment with N-ethyl-N-nitrosourea (ENU)-exposed rats - Stephanie L. Smith-Roe; Cheryl A. Hobbs; Victoria Hull; J. Todd Auman; Leslie Recio; Michael A. Streicker; Miriam V. Rivas; Gabriel A. Pratt; Fang Yin Lo; Jacob E. Higgins; Elizabeth K. Schmidt; Lindsey N. Williams; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Turning the tide on sex and the microbiota in aquatic animals - Kieran A. Bates; Chelsea Higgins; Maurine Neiman; Kayla C. King (Hydrobiologia, 2023)
Sex-based differences in animal microbiota are increasingly recognized as of biological importance. While most animal biomass is found in aquatic ecosystems and many water-dwelling species are of high economic and ecological value, biological sex is rarely included as an explanatory variable in studies of the aquatic animal microbiota. In this opinion piece, we argue for greater consideration of host sex in studying the microbiota of aquatic animals, emphasizing the many advancements that this information could provide in the life sciences, from the evolution of sex to aquaculture.

Genomic approaches to mitigating genetic diversity loss in declining populations - Christen M. Bossu; Marina Rodriguez; Christine Rayne; Debra A. Chromczak; Philip G. Higgins; Lynne A. Trulio; Kristen C. Ruegg (Molecular Ecology, 2023)
The accelerating pace of global biodiversity loss is exacerbated by habitat fragmentation and subsequent inbreeding in small populations. To address this problem, conservation practitioners often turn to assisted breeding programmes with the aim of enhancing genetic diversity in declining populations. Although genomic information is infrequently included in these efforts, it has the potential to significantly enhance the success of such programmes. In this study, we showcase the value of genomic approaches for increasing genetic diversity in assisted breeding efforts, specifically focusing on a highly inbred population of Western burrowing owls. To maximize genetic diversity in the resulting offspring, we begin by creating an optimal pairing decision tree based on sex, kinship and patterns of homozygosity across the genome. To evaluate the effectiveness of our strategy, we compare genetic diversity, brood size and nestling success rates between optimized and non‐optimized pairs. Additionally, we leverage recently discovered correlations between telomere length and fitness across species to investigate whether genomic optimization could have long‐term fitness benefits. Our results indicate that pairing individuals with contrasting patterns of homozygosity across the genome is an effective way to increase genetic diversity in offspring. Although short‐term field‐based metrics of success did not differ significantly between optimized and non‐optimized pairs, offspring from optimized pairs had significantly longer telomeres, suggesting that genetic optimization can help reduce the risk of inbreeding depression. These findings underscore the importance of genomic tools for informing efforts to preserve the adaptive potential of small, inbred populations at risk of further decline.

Landscape fires disproportionally affect high conservation value temperate peatlands, meadows, and deciduous forests, but only under low moisture conditions - Máire Kirkland; Philip W. Atkinson; James W. Pearce-Higgins; Mark C. de Jong; Thomas P.F. Dowling; Dmitri Grummo; Megan Critchley; Adham Ashton-Butt (Science of The Total Environment, 2023)

Correction to: Like Frying Multiple Eggs in One Pan: a Qualitative Study Exploring the Understanding of Inter-speciality Training in Cancer Care - W. McInally; K. Benstead; A. Brandl; N. Dodlek; J. De Munter; C. Gasparotto; J. Grau-Eriksen; R. G. Kelly; C. Lecoq; N. O’Higgins; K. Oliver; M. Popovics; et al. (Journal of Cancer Education, 2023)

Like Frying Multiple Eggs in One Pan: a Qualitative Study Exploring the Understanding of Inter-speciality Training in Cancer Care - W. McInally; K. Benstead; A. Brandl; N. Dodlek; J. De Munter; C. Gasparotto; J. Grau-Eriksen; R. G. Kelly; C. Lecoq; N. O’Higgins; K. Oliver; M. Popovics; et al. (Journal of Cancer Education, 2023)
H igh-quality cancer care is a key priority worldwide. Caring for people affected by cancer requires a range of specific knowledge, skills and experience to deliver the complex care regimens both within the hospital and within the community environment. In June 2022, the European Cancer Organisation along with 33 European cancer societies began working together to develop a curriculum for inter-speciality training for healthcare professionals across Europe. As part of the project, this research consisted of a qualitative survey distributed to the European Union societies via email. The aim of this paper is to disseminate the qualitative findings from healthcare professionals across Europe. Questionnaires were sent out to a convenience sample of 219 healthcare professionals and patient advocates with a response rate of 55% ( n = 115). The findings identified that there were four key themes: ‘What is inter-speciality training?’, ‘Barriers and challenges’, ‘Support throughout the cancer journey’ and ‘New ways of working’. These results are part of a larger needs analysis and scoping review to inform the development of a core competency framework which will be part of an inter-speciality curriculum for specialist cancer doctors, nurses and other healthcare professionals across Europe. Healthcare professionals will be able to access education and training through the virtual learning environment and workshops and by clinical rotations to other specialties.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Identification of genetic loci in lettuce mediating quantitative resistance to fungal pathogens - Harry Pink; Adam Talbot; Abi Graceson; Juliane Graham; Gill Higgins; Andrew Taylor; Alison C. Jackson; Maria Truco; Richard Michelmore; Chenyi Yao; Frances Gawthrop; David Pink; et al. (Theoretical and Applied Genetics, 2022)
Key message We demonstrate genetic variation for quantitative resistance against important fungal pathogens in lettuce and its wild relatives, map loci conferring resistance and predict key molecular mechanisms using transcriptome profiling. Abstract Lactuca sativa L. (lettuce) is an important leafy vegetable crop grown and consumed globally. Chemicals are routinely used to control major pathogens, including the causal agents of grey mould ( Botrytis cinerea ) and lettuce drop ( Sclerotinia sclerotiorum ) . With increasing prevalence of pathogen resistance to fungicides and environmental concerns, there is an urgent need to identify sources of genetic resistance to B. cinerea and S. sclerotiorum in lettuce. We demonstrated genetic variation for quantitative resistance to B. cinerea and S. sclerotiorum in a set of 97 diverse lettuce and wild relative accessions, and between the parents of lettuce mapping populations. Transcriptome profiling across multiple lettuce accessions enabled us to identify genes with expression correlated with resistance, predicting the importance of post-transcriptional gene regulation in the lettuce defence response. We identified five genetic loci influencing quantitative resistance in a F 6 mapping population derived from a Lactuca serriola (wild relative) × lettuce cross, which each explained 5–10% of the variation. Differential gene expression analysis between the parent lines, and integration of data on correlation of gene expression and resistance in the diversity set, highlighted potential causal genes underlying the quantitative trait loci.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Variation of plagioclase shape with size in intermediate magmas: a window into incipient plagioclase crystallisation - Martin F. Mangler; Madeleine C. S. Humphreys; Fabian B. Wadsworth; Alexander A. Iveson; Michael D. Higgins (Contributions to Mineralogy and Petrology, 2022)
Volcanic rocks commonly display complex textures acquired both in the magma reservoir and during ascent to the surface. While variations in mineral compositions, sizes and number densities are routinely analysed to reconstruct pre-eruptive magmatic histories, crystal shapes are often assumed to be constant, despite experimental evidence for the sensitivity of crystal habit to magmatic conditions. Here, we develop a new program ( ShapeCalc ) to calculate 3D shapes from 2D crystal intersection data and apply it to study variations of crystal shape with size for plagioclase microlites ( l < 100 µm) in intermediate volcanic rocks. The smallest crystals tend to exhibit prismatic 3D shapes, whereas larger crystals ( l > 5–10 µm) show progressively more tabular habits. Crystal growth modelling and experimental constraints indicate that this trend reflects shape evolution during plagioclase growth, with initial growth as prismatic rods and subsequent preferential overgrowth of the intermediate dimension to form tabular shapes. Because overgrowth of very small crystals can strongly affect the external morphology, plagioclase microlite shapes are dependent on the available growth volume per crystal, which decreases during decompression-driven crystallisation as crystal number density increases. Our proposed growth model suggests that the range of crystal shapes developed in a magma is controlled by the temporal evolution of undercooling and total crystal numbers, i.e., distinct cooling/decompression paths. For example, in cases of slow to moderate magma ascent rates and quasi-continuous nucleation, early-formed crystals grow larger and develop tabular shapes, whereas late-stage nucleation produces smaller, prismatic crystals. In contrast, rapid magma ascent may suppress nucleation entirely or, if stalled at shallow depth, may produce a single nucleation burst associated with tabular crystal shapes. Such variation in crystal shapes have diagnostic value and are also an important factor to consider when constructing CSDs and models involving magma rheology.

Climate change research and action must look beyond 2100 - Christopher Lyon; Erin E. Saupe; Christopher J. Smith; Daniel J. Hill; Andrew P. Beckerman; Lindsay C. Stringer; Robert Marchant; James McKay; Ariane Burke; Paul O’Higgins; Alexander M. Dunhill; Bethany J. Allen; et al. (Global Change Biology, 2022)
Anthropogenic activity is changing Earth's climate and ecosystems in ways that are potentially dangerous and disruptive to humans. Greenhouse gas concentrations in the atmosphere continue to rise, ensuring that these changes will be felt for centuries beyond 2100, the current benchmark for projection. Estimating the effects of past, current, and potential future emissions to only 2100 is therefore short‐sighted. Critical problems for food production and climate‐forced human migration are projected to arise well before 2100, raising questions regarding the habitability of some regions of the Earth after the turn of the century. To highlight the need for more distant horizon scanning, we model climate change to 2500 under a suite of emission scenarios and quantify associated projections of crop viability and heat stress. Together, our projections show global climate impacts increase significantly after 2100 without rapid mitigation. As a result, we argue that projections of climate and its effects on human well‐being and associated governance and policy must be framed beyond 2100.

Aging induced by D-galactose aggravates cardiac dysfunction via exacerbating mitochondrial dysfunction in obese insulin-resistant rats - Cherry Bo-Htay; Thazin Shwe; Louis Higgins; Siripong Palee; Krekwit Shinlapawittayatorn; Siriporn C Chattipakorn; Nipon Chattipakorn (GeroScience, 2020)

Variable hybridization outcomes in trout are predicted by historical fish stocking and environmental context - Elizabeth G. Mandeville; Annika W. Walters; Brittany J. Nordberg; Karly H. Higgins; Jason C. Burckhardt; Catherine E. Wagner (Molecular Ecology, 2019)
Hybridization can profoundly affect the genomic composition and phenotypes of closely related species, and provides an opportunity to identify mechanisms that maintain reproductive isolation between species. Recent evidence suggests that hybridization outcomes within a species pair can vary across locations. However, we still do not know how variable outcomes of hybridization are across geographic replicates, and what mechanisms drive that variation. In this study, we described hybridization outcomes across 27 locations in the North Fork Shoshone River basin (Wyoming, USA) where native Yellowstone cutthroat trout and introduced rainbow trout co‐occur. We used genomic data and hierarchical Bayesian models to precisely identify ancestry of hybrid individuals. Hybridization outcomes varied across locations. In some locations, only rainbow trout and advanced backcrossed hybrids towards rainbow trout were present, while trout in other locations had a broader range of ancestry, including both parental species and first‐generation hybrids. Later‐generation intermediate hybrids were rare relative to backcrossed hybrids and rainbow trout individuals. Using an individual‐based simulation, we found that outcomes of hybridization in the North Fork Shoshone River basin deviate substantially from what we would expect under null expectations of random mating and no selection against hybrids. Since this deviation implies that some mechanisms of reproductive isolation function to maintain parental taxa and a diversity of hybrid types, we then modelled hybridization outcomes as a function of environmental variables and stocking history that are likely to affect prezygotic barriers to hybridization. Variables associated with history of fish stocking were the strongest predictors of hybridization outcomes, followed by environmental variables that might affect overlap in spawning time and location.

Long-Term Responses of Nutrient Budgets to Concurrent Climate-Related Stressors in a Boreal Watershed - Craig A. Emmerton; Ken G. Beaty; Nora J. Casson; Jennifer A. Graydon; Raymond H. Hesslein; Scott N. Higgins; Hisham Osman; Michael J. Paterson; Andrew Park; Jacques C. Tardif (Ecosystems, 2019)

Site-based adaptation reduces the negative effects of weather upon a southern range margin Welsh black grouse Tetrao tetrix population that is vulnerable to climate change - James W. Pearce-Higgins; Patrick J. Lindley; Ian G. Johnstone; Reg I. Thorpe; David J.T. Douglas; Murray C. Grant (Climatic Change, 2019)

A high resolution measurement of the morning ABL transition using distributed temperature sensing and an unmanned aircraft system - C. W. Higgins; M. G. Wing; J. Kelley; C. Sayde; J. Burnett; H. A. Holmes (Environmental Fluid Mechanics, 2018)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Response to varying the nicotine content of cigarettes in vulnerable populations: an initial experimental examination of acute effects - Stephen T. Higgins; Sarah H. Heil; Stacey C. Sigmon; Jennifer W. Tidey; Diann E. Gaalema; Maxine L. Stitzer; Hanna Durand; Janice Y. Bunn; Jeff S. Priest; Christopher A. Arger; Mollie E. Miller; Cecilia L. Bergeria; et al. (Psychopharmacology, 2017)

Allometric equations for integrating remote sensing imagery into forest monitoring programmes - Tommaso Jucker; John Caspersen; Jérôme Chave; Cécile Antin; Nicolas Barbier; Frans Bongers; Michele Dalponte; Karin Y. van Ewijk; David I. Forrester; Matthias Haeni; Steven I. Higgins; Robert J. Holdaway; et al. (Global Change Biology, 2017)
Remote sensing is revolutionizing the way we study forests, and recent technological advances mean we are now able – for the first time – to identify and measure the crown dimensions of individual trees from airborne imagery. Yet to make full use of these data for quantifying forest carbon stocks and dynamics, a new generation of allometric tools which have tree height and crown size at their centre are needed. Here, we compile a global database of 108753 trees for which stem diameter, height and crown diameter have all been measured, including 2395 trees harvested to measure aboveground biomass. Using this database, we develop general allometric models for estimating both the diameter and aboveground biomass of trees from attributes which can be remotely sensed – specifically height and crown diameter. We show that tree height and crown diameter jointly quantify the aboveground biomass of individual trees and find that a single equation predicts stem diameter from these two variables across the world's forests. These new allometric models provide an intuitive way of integrating remote sensing imagery into large‐scale forest monitoring programmes and will be of key importance for parameterizing the next generation of dynamic vegetation models.

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Soil Nailing in Dublin Boulder Clay - C. O. Menkiti; M. Long; G. W. E. Milligan; P. Higgins (Geotechnical and Geological Engineering, 2014)

The outcome and long-term follow-up of 94 patients with recurrent and refractory Clostridium difficile infection using single to multiple fecal microbiota transplantation via retention enema - C. H. Lee; J. E. Belanger; Z. Kassam; M. Smieja; D. Higgins; G. Broukhanski; P. T. Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Mechanisms underpinning climatic impacts on natural populations: altered species interactions are more important than direct effects - Nancy Ockendon; David J. Baker; Jamie A. Carr; Elizabeth C. White; Rosamunde E. A. Almond; Tatsuya Amano; Esther Bertram; Richard B. Bradbury; Cassie Bradley; Stuart H. M. Butchart; Nathalie Doswald; Wendy Foden; et al. (Global Change Biology, 2014)
Shifts in species' distribution and abundance in response to climate change have been well documented, but the underpinning processes are still poorly understood. We present the results of a systematic literature review and meta‐analysis investigating the frequency and importance of different mechanisms by which climate has impacted natural populations. Most studies were from temperate latitudes of North America and Europe; almost half investigated bird populations. We found significantly greater support for indirect, biotic mechanisms than direct, abiotic mechanisms as mediators of the impact of climate on populations. In addition, biotic effects tended to have greater support than abiotic factors in studies of species from higher trophic levels. For primary consumers, the impact of climate was equally mediated by biotic and abiotic mechanisms, whereas for higher level consumers the mechanisms were most frequently biotic, such as predation or food availability. Biotic mechanisms were more frequently supported in studies that reported a directional trend in climate than in studies with no such climatic change, although sample sizes for this comparison were small. We call for more mechanistic studies of climate change impacts on populations, particularly in tropical systems.

Gene expression in closely related species mirrors local adaptation: consequences for responses to a warming world - Shawn T. O'Neil; Jason D. K. Dzurisin; Caroline M. Williams; Neil F. Lobo; Jessica K. Higgins; Jillian M. Deines; Rory D. Carmichael; Erliang Zeng; John C. Tan; Grace C. Wu; Scott J. Emrich; Jessica J. Hellmann (Molecular Ecology, 2014)
Local adaptation of populations could preclude or slow range expansions in response to changing climate, particularly when dispersal is limited. To investigate the differential responses of populations to changing climatic conditions, we exposed poleward peripheral and central populations of two L epidoptera to reciprocal, common‐garden climatic conditions and compared their whole‐transcriptome expression. We found evidence of simple population differentiation in both species, and in the species with previously identified population structure and phenotypic local adaptation, we found several hundred genes that responded in a synchronized and localized fashion. These genes were primarily involved in energy metabolism and oxidative stress, and expression levels were most divergent between populations in the same environment in which we previously detected divergence for metabolism. We found no localized genes in the species with less population structure and for which no local adaptation was previously detected. These results challenge the assumption that species are functionally similar across their ranges and poleward peripheral populations are preadapted to warmer conditions. Rather, some taxa deserve population‐level consideration when predicting the effects of climate change because they respond in genetically based, distinctive ways to changing conditions.

Atmospheric impacts of an Arctic sea ice minimum as seen in the Community Atmosphere Model - Elizabeth N. Cassano; John J. Cassano; Matthew E. Higgins; Mark C. Serreze (International Journal of Climatology, 2014)
There is growing recognition that reductions in Arctic sea ice extent will influence patterns of atmospheric circulation both within and beyond the Arctic. We explore the impact of 2007 ice conditions (the second lowest Arctic sea ice extent in the satellite era) on atmospheric circulation and surface temperatures and fluxes through a series of model experiments with the NCAR Community Atmospheric Model version 3 ( CAM3 ). Two 30‐year simulations were performed; one using climatological sea ice extent for the end of the 20th century and other using observed sea ice extent from 2007. Circulation differences over the Northern Hemisphere were most prominent during autumn and winter with lower sea level pressure ( SLP ) and tropospheric pressure simulated over much of the Arctic for the 2007 sea ice experiment. The atmospheric response to 2007 ice conditions was much weaker during summer, with negative SLP anomalies simulated from Alaska across the Arctic to Greenland. Higher temperatures and larger surface fluxes to the atmosphere in areas of anomalous open water were also simulated. CAM3 experiment results were compared to observed SLP anomalies from the National Center for Environmental Prediction/National Center for Atmospheric Research ( NCEP / NCAR ) Reanalysis data. The observed SLP anomalies during spring are nearly opposite to those simulated. In summer, large differences were shown between the observed and simulated SLP also, suggesting that the sea ice conditions in the months preceding and during the summer of 2007 were not responsible for creating an atmospheric circulation pattern which favoured the large observed sea ice loss. The simulated and observed atmospheric circulation anomalies during autumn and winter were more similar than spring and summer, with the exception of a strong high pressure system in the Beaufort Sea which was not simulated, suggesting that the forced atmospheric response to reduced sea ice was in part responsible for the observed atmospheric circulation anomalies during autumn and winter.

Quantifying temporal variability in the metacommunity structure of stream fishes: the influence of non-native species and environmental drivers - T. Erős; P. Sály; P. Takács; C. L. Higgins; P. Bíró; D. Schmera (Hydrobiologia, 2014)

Divergent evolutionary processes associated with colonization of offshore islands - Natália Martínková; Ross Barnett; Thomas Cucchi; Rahel Struchen; Marine Pascal; Michel Pascal; Martin C. Fischer; Thomas Higham; Selina Brace; Simon Y. W. Ho; Jean‐Pierre Quéré; Paul O'Higgins; et al. (Molecular Ecology, 2013)
Oceanic islands have been a test ground for evolutionary theory, but here, we focus on the possibilities for evolutionary study created by offshore islands. These can be colonized through various means and by a wide range of species, including those with low dispersal capabilities. We use morphology, modern and ancient sequences of cytochrome b ( cytb ) and microsatellite genotypes to examine colonization history and evolutionary change associated with occupation of the O rkney archipelago by the common vole ( M icrotus arvalis ), a species found in continental E urope but not in B ritain. Among possible colonization scenarios, our results are most consistent with human introduction at least 5100 bp (confirmed by radiocarbon dating). We used approximate B ayesian computation of population history to infer the coast of Belgium as the possible source and estimated the evolutionary timescale using a Bayesian coalescent approach. We showed substantial morphological divergence of the island populations, including a size increase presumably driven by selection and reduced microsatellite variation likely reflecting founder events and genetic drift. More surprisingly, our results suggest that a recent and widespread cytb replacement event in the continental source area purged cytb variation there, whereas the ancestral diversity is largely retained in the colonized islands as a genetic ‘ark’. The replacement event in the continental M . arvalis was probably triggered by anthropogenic causes (land‐use change). Our studies illustrate that small offshore islands can act as field laboratories for studying various evolutionary processes over relatively short timescales, informing about the mainland source area as well as the island.

Characterization of water and wildlife strains as a subgroup of C ampylobacter jejuni using DNA microarrays - Richard A. Stabler; Jonas T. Larsson; Suaad Al‐Jaberi; Eva M. Nielsen; Emily Kay; Clarence C. Tam; Craig D. Higgins; Laura C. Rodrigues; Judith F. Richardson; Sarah J. O'Brien; Brendan W. Wren (Environmental Microbiology, 2013)
Summary C ampylobacter jejuni is the leading cause of human bacterial gastroenteritis worldwide, but source attribution of the organism is difficult. Previously, DNA microarrays were used to investigate isolate source, which suggested a non‐livestock source of infection. In this study we analysed the genome content of 162 clinical, livestock and water and wildlife ( WW ) associated isolates combined with the previous study. Isolates were grouped by genotypes into nine clusters ( C 1 to C 9). Multilocus sequence typing ( MLST ) data demonstrated that livestock associated clonal complexes dominated clusters C 1– C 6. The majority of WW isolates were present in the C 9 cluster. Analysis of previously reported genomic variable regions demonstrated that these regions were linked to specific clusters. Two novel variable regions were identified. A six gene multiplex PCR ( mPCR ) assay, designed to effectively differentiated strains into clusters, was validated with 30 isolates. A further five WW isolates were tested by m PCR and were assigned to the C 7‐ C 9 group of clusters. The predictive mPCR test could be used to indicate if a clinical case has come from domesticated or WW sources. Our findings provide further evidence that WW C . jejuni subtypes show niche adaptation and may be important in causing human infection.

Influence of competition and rainfall manipulation on the growth responses of savanna trees and grasses - Edmund C. February; Steven I. Higgins; William J. Bond; Louise Swemmer (Ecology, 2013)
In this study, we explored how rainfall manipulation influenced competitive interactions between grasses and juvenile trees (small nonreproductive trees capable of resprouting) in savanna. To do this, we manipulated rainfall amount in the field using an incomplete factorial experiment that determined the effects of rainfall reduction, no manipulation, rainfall addition, and competition between grasses and trees on grass and tree growth. As response variables, we focused on several measures of tree growth and Disc Pasture Meter settling height as an estimate of grass aboveground biomass. We conducted the study over four years, at two sites in the Kruger National Park, South Africa. Our results show that rainfall manipulation did not have substantial effects on any of the measures of tree growth we considered. However, trees at plots where grasses had been removed grew on average 15 cm more in height and 1.3–1.7 times more in basal area per year than those in plots with grasses. Grass biomass was not influenced by the presence of trees but was significantly and positively influenced by rainfall addition. These findings were not fundamentally influenced by soil type or by prevailing precipitation, suggesting applicability of our results to a wide range of savannas. Our results suggest that, in savannas, increasing rainfall serves to increase the competitive pressure exerted by grasses on trees. The implication is that recruitment into the adult tree stage from the juvenile stage is most likely in drought years when there is little competition from grass for resources and grass fuel loads are low.

Virtual Functional Morphology: Novel Approaches to the Study of Craniofacial Form and Function - Paul O’Higgins; Laura C. Fitton; Roger Phillips; JunFen Shi; Jia Liu; Flora Gröning; Samuel N. Cobb; Michael J. Fagan (Evolutionary Biology, 2012)

Development of eight polymorphic microsatellite loci in the cephalopod Octopus pallidus - K. L. Higgins; C. P. Burridge (Conservation Genetics Resources, 2012)

The cell adhesion gene PVRL3 is associated with congenital ocular defects - Salil A. Lachke; Anne W. Higgins; Maiko Inagaki; Irfan Saadi; Qiongchao Xi; Michelle Long; Bradley J. Quade; Michael E. Talkowski; James F. Gusella; Atsuko Fujimoto; Michael L. Robinson; Ying Yang; et al. (Human Genetics, 2012)

Ecological Adaptations of Mandibular Form in Fissiped Carnivora - C. Meloro; P. O’Higgins (Journal of Mammalian Evolution, 2011)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Development and Experimental Validation of a 20K Atlantic Cod (Gadus morhua) Oligonucleotide Microarray Based on a Collection of over 150,000 ESTs - Marije Booman; Tudor Borza; Charles Y. Feng; Tiago S. Hori; Brent Higgins; Adrian Culf; Daniel Léger; Ian C. Chute; Anissa Belkaid; Marlies Rise; A. Kurt Gamperl; Sophie Hubert; et al. (Marine Biotechnology, 2011)

How do frequent fires in the Cerrado alter the lepidopteran community? - I. R. Diniz; B. Higgins; H. C. Morais (Biodiversity and Conservation, 2011)

An Integrated Approach to Gene Discovery and Marker Development in Atlantic Cod (Gadus morhua) - Sharen Bowman; Sophie Hubert; Brent Higgins; Cynthia Stone; Jennifer Kimball; Tudor Borza; Jillian Tarrant Bussey; Gary Simpson; Catherine Kozera; Bruce A. Curtis; Jennifer R. Hall; Tiago S. Hori; et al. (Marine Biotechnology, 2011)

Age-related changes in short-latency motor cortex inhibition - Ashleigh E. Smith; Michael C. Ridding; Ryan D. Higgins; Gary A. Wittert; Julia B. Pitcher (Experimental Brain Research, 2009)

Microsatellite markers for the wood decay fungus Phlebiopsis gigantea - Ai-Zhong Liu; Nicklas Samils; Brian Higgins; Jan Stenlid; Bernard Slippers; C. Joseph Nairn; Sarah F. Covert (Conservation Genetics, 2009)

Does climate change explain the decline of a trans-Saharan Afro-Palaearctic migrant? - J. W. Pearce-Higgins; D. W. Yalden; T. W. Dougall; C. M. Beale (Oecologia, 2009)

Exploring gene-environment interactions in Parkinson’s disease - Colin C. McCulloch; Denise M. Kay; Stewart A. Factor; Ali Samii; John G. Nutt; Donald S. Higgins; Alida Griffith; John W. Roberts; Berta C. Leis; Jennifer S. Montimurro; Cyrus P. Zabetian; Haydeh Payami (Human Genetics, 2008)

Tree distribution on a steep environmental gradient in an arid savanna - Edmund C. February; Steven I. Higgins; Rosemary Newton; Adam G. West (Journal of Biogeography, 2007)
Aim The structure of savannas ranges from scrub to woodland over broad geographical gradients. Here we examine the hypothesis that water availability is a major determinant of these structural differences by ascertaining the relationship between water availability and tree growth across a steep moisture gradient. Location The study site is a sub‐tropical savanna, with a mean annual precipitation of 400 mm, located in the Phugwane river basin, Kruger National Park, Limpopo Province, South Africa. Methods We determined plant moisture stress using xylem pressure potentials, stem growth using dendrometer bands, and estimated the water sources available to plants using stable hydrogen and oxygen isotope ratios. The primary objective was to understand tree growth relative to available water along an environmental gradient. Results We found that Philenoptera violacea trees growing close to the stream have lower water stress (least negative xylem pressure potentials) and higher cumulative growth than those growing away from the stream. The stem growth of P. violacea was characterized by steady incremental growth and could not be related to antecedent rainfall. Colophospermum mopane trees experienced higher water stress, yet trees growing adjacent to the stream achieved the highest cumulative growth rates over the study period. The growth of C. mopane could be clearly linked to antecedent rainfall, and most growth was achieved during short growth pulses that followed rainfall events. δ 18 O values become progressively more enriched in the heavier isotope with distance from the stream, suggesting that access to groundwater decreases with distance from the stream side. The isotopic data suggest that P. violacea has access to groundwater, but that C. mopane does not. Main conclusions Our results show that water stress increases with distance from the stream side as a result of reduced access to groundwater. Trees without access to deep water adopt an opportunistic growth strategy.

Who Needs to Spend Money on Conservation Science Anyway? - Jonathan V. Higgins; Jerome L. Touval; Robert S. Unnasch; Steffen Reichle; David C. Oren; William R. Waldman; Jonathan M. Hoekstra (Conservation Biology, 2006)

The antinociceptive and anxiolytic-like effects of the metabotropic glutamate receptor 5 (mGluR5) antagonists, MPEP and MTEP, and the mGluR1 antagonist, LY456236, in rodents: a comparison of efficacy and side-effect profiles - Geoffrey B. Varty; Mariagrazia Grilli; Angelo Forlani; Silva Fredduzzi; Michael E. Grzelak; Donald H. Guthrie; Robert A. Hodgson; Sherry X. Lu; Elisa Nicolussi; Annamarie J. Pond; Eric M. Parker; John C. Hunter; et al. (Psychopharmacology, 2005)

Alignment Trends of Velocity Gradients and Subgrid-Scale Fluxes in the Turbulent Atmospheric Boundary Layer - Chad W. Higgins; Marc B. Parlange; C. Meneveau (Boundary-Layer Meteorology, 2003)

Confirmation and high resolution mapping of an atherosclerosis susceptibility gene in mice on Chromosome 1 - Shelley A. Phelan; David R. Beier; David C. Higgins; Beverly Paigen (Mammalian Genome, 2002)

Fine mapping of Ath6, a quantitative trait locus for atherosclerosis in mice - Maureen K. Purcell; Jian-Long Mu; David C. Higgins; Ramu Elango; Harry Whitmore; Stephen Harris; Beverly Paigen (Mammalian Genome, 2001)

d -Amphetamine increases choice of cigarette smoking over monetary reinforcement - Jennifer W. Tidey; Stephen T. Higgins; Suzanne C. O'Neill (Psychopharmacology, 2000)

Sampling Strategies for Mapping Soil Phosphorus and Soil Potassium Distributions in Cool Temperate Grassland - Z. Shi; K. Wang; J. S. Bailey; C. Jordan; A. J. Higgins (Precision Agriculture, 2000)

Empirical Models for Predicting the Dry Matter Yield of Grass Silage Swards Using Plant Tissue Analyses - J. S. Bailey; A. Higgins; C. Jordan (Precision Agriculture, 2000)

PCR rescue and analysis of transgene sequences directly from crude extracts of transgenic embryos and plants - C. M. Higgins; R. M. Hall; P. R. Campbell; R. G. Dietzgen (Plant Molecular Biology Reporter, 2000)

An edited linkage map for the AXB and BXA recombinant inbred mouse strains - Stephen B. Sampson; David C. Higgins; Rosemary W. Elliot; Benjamin A. Taylor; Kira K. Lueders; Robert A. Koza; Beverly Paigen (Mammalian Genome, 1998)

Sequences of the coat protein gene of five peanut stripe virus (PStV) strains from Thailand and their evolutionary relationship with other bean common mosaic virus sequences - C. M. Higgins; B. G. Cassidy; P.-Y. Teycheney; S. Wongkaew; R. G. Dietzgen (Archives of Virology, 1998)

An additional 150 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - David C. Higgins; Beverly Paigen (Mammalian Genome, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

RNAs 4A and 5 are present in tomato aspermy virusand both subgroups of cucumber mosaic virus - C. L. Blanchard; T. J. V. Higgins; B. J. Anderson (Archives of Virology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Effect of sunscreens, irradiance and resting periods on the germination ofMetarhizium flavoviride conidia - T. R. Hunt; D. Moore; P. M. Higgins; C. Prior (BioControl, 1994)

Detection of antibodies to caprine arthritis-encephalitis virus using recombinant gag proteins - E. Rimstad; N. East; E. DeRock; J. Higgins; N. C. Pedersen (Archives of Virology, 1994)

A host-cell-selected variant of influenza B virus with a single nucleotide substitution in HA affecting a potential glycosylation site was attentuated in virulence for volunteers - J. S. Oxford; G. C. Schild; T. Corcoran; R. Newman; D. Major; J. Robertson; J. Bootman; P. Higgins; W. Al-Nakib; D. A. J. Tyrrell (Archives of Virology, 1990)

Subunit hybridization and immunological studies of duplicated phosphoglucose isomerase isozymes - R. C. Higgins; L. D. Gottlieb (Biochemical Genetics, 1984)